2001
DOI: 10.1038/sj.bjp.0703814
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms underlying migrating motor complex formation in mouse isolated colon

Abstract: 1 Little is known about the intrinsic enteric re¯ex pathways associated with migrating motor complex (MMC) formation. Acetylcholine (ACh) mediates the rapid component of the MMC, however a non-cholinergic component also exists. The present study investigated the possible role of endogenous tachykinins (TKs) in the formation of colonic MMCs and the relative roles of excitatory and inhibitory pathways. 2 MMCs were recorded from the circular muscle at four sites (proximal, proximal-mid, mid-distal and distal) alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 38 publications
9
79
1
Order By: Relevance
“…Addition of the NK 2 antagonist GR159897 decreasedfecal pellet motility in3 month colons but was without effect in the 24 month group consistent with NK 2 -mediated signaling being naturally impaired in this age group. These results support those from other studies,which have also shown that NK 2 blockade can reduce the amplitude of colonic migrating motor complexes (CMMCs), a motility pattern believed to contribute to fecal pellet propulsion (Brierley et al, 2001). The precise causes ofthe decrease in NK 2 -mediated signaling are unclear and may possibly reflect the loss of myenteric neurones,whichhas been recorded in many species including humans (Saffrey, 2013).However, we have recently shown that myenteric neuronal numbers do not decrease with age in the distal colon of the C57BL/6J male mice suggesting that the changes observed reflect the altered functioning of a fixed neuronal pool (Gamage et al, 2013).…”
Section: Accepted M Manuscriptsupporting
confidence: 82%
See 1 more Smart Citation
“…Addition of the NK 2 antagonist GR159897 decreasedfecal pellet motility in3 month colons but was without effect in the 24 month group consistent with NK 2 -mediated signaling being naturally impaired in this age group. These results support those from other studies,which have also shown that NK 2 blockade can reduce the amplitude of colonic migrating motor complexes (CMMCs), a motility pattern believed to contribute to fecal pellet propulsion (Brierley et al, 2001). The precise causes ofthe decrease in NK 2 -mediated signaling are unclear and may possibly reflect the loss of myenteric neurones,whichhas been recorded in many species including humans (Saffrey, 2013).However, we have recently shown that myenteric neuronal numbers do not decrease with age in the distal colon of the C57BL/6J male mice suggesting that the changes observed reflect the altered functioning of a fixed neuronal pool (Gamage et al, 2013).…”
Section: Accepted M Manuscriptsupporting
confidence: 82%
“…Tachykinins are one of theimportant regulators of colonic motility in mice (Brierley et al, 2001;Deiteren et al, 2011;Mulè et al, 2007). Tachykininsregulate colonic motility via NK 1 and NK 2 receptors.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This similarity is so strong that the colonic propagating contraction complexes are usually termed colonic MMCs, although they may actually be analogues of mass-movement contractions involved in defecation. Whereas IJPs are seen in the mouse colon, apamin does not affect colonic MMC cycling frequency or propagation speeds and has inconsistent effects on contraction amplitude [132,136,137].…”
Section: Functional Roles Of Purinergic Ijpsmentioning
confidence: 93%
“…Colonic migrating motor complexes (CMMCs) result from a complicated interplay between enteric afferent neurons, interneurons, and motor neurons and comprise a major motor pattern involved in moving fecal matter along the bowel (24)(25)(26). In the current study, CMMCs were studied using previously described methods (20,27,28) with minor modifications. Male BALB/c, C57BL/6, and M2R-or M3R-knockout mice (ages 10-12 weeks, 20-30 gm) were killed and the colons excised and suspended in a 100-ml organ bath containing Krebs-Ringer solution with 95% O 2 /5% CO 2 (pH 7.4) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…In this assay, spontaneous, regular CMMCs were recorded as contractions migrating from the proximal to the distal colon at intervals of 2-3 minutes, separated by periods of quiescence, during which inhibitory motor activity occurs (28,35) (Figures 1A and 4A). …”
Section: Park Et Almentioning
confidence: 99%